The Effectiveness of Using Shadowing Technique Towards Students’ Pronunciation Skill - Suyadi, Suyadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study investigates the efficacy of the shadowing technique in enhancing students' pronunciation skills. The shadowing technique involves learners mimicking a native speaker in real-time to improve pronunciation accuracy and fluency. Through a controlled experiment with 31 students and 30 students as experimental group, the study evaluates the impact of shadowing on students' pronunciation proficiency compared to traditional teaching methods. The technique of collecting data was taken directly when the students said the words. Results indicate a significant improvement in pronunciation accuracy and fluency among participants who engaged in shadowing exercises, suggesting its effectiveness as a pedagogical tool for enhancing pronunciation skills. Implications for language teaching and learning are discussed.